Pertumbuhan In Vitro Biji Buah Naga Merah (Hylocereus polyrhizusWebb. Britton &Rose ) dengan Penambahan Air Kelapa dan Naphthalene Acetic Acid (NAA) - Mukarlina, Finna, Riza Linda, (Jurnal Protobiont, 2015)
The dragon fruit, also known as the red pitaya, (Hylocereus polyrhizus Webb. Britton & Rose) is one of the plants which can easily be cultivated in Indonesia. Seed multiplication through the in vitro tissue culture technology is the right alternative for supplying seedlings in a large number and in a relatively short time. This research aimed to find out the effect of adding coconut water and NAA, as well as to find out the most optimal concentrations of coconut water and NAA for the growth of the dragon fruit (H. polyrhizus) on the in vitro culture medium. This research was carried out for five months from January to May 2015 at the Laboratory of Tissue Culture of the Aloe Vera Center Pontianak. The experiment used the Completely Randomized Factorial Design with 2 treatments. The first factor was the coconut water with concentrations of 0%, 5%, 10%,Â  15%, and the second factor was the NAA with concentrations of 0 M, 5.10-6 M, 10-6 M,Â  10-7 M. The research findings showed that the addition of coconut water and NAA had an effect on the height growth of the dragon fruit (H. polyrhizus) especially at low concentrations, i.e. 5% of coconut water, 10-7 of NAA, and a combination of both at concentrations of 10% coconut water and 10-6 NAA.